Brand Image dalam Kajian Filsafat Ilmu - Haryanto, Totok; Harsono, Mugi (Jurnal Manajemen Bisnis dan Keuangan, 2022)
The study of theory and practice in marketing has explored and provided an operational definition of brand image which is one of the most extensive and intensive constructs. The purpose of this study is to describe the brand image in the study of the philosophy of science. This study will explain the brand image which will be explained from the aspects of ontology, epistemology, and axiology. The methodology in this study is to conduct a literature review from empirical sources or previous research. This study produces a conceptual model of age and gender variables that moderate the influence of brand image and brand personality on brand loyalty which affects brand equity.